Evidence of effectiveness of management excellence practices used by organisations of the third sector. (2017) - Vasconcelos, Ana Lúcia Fontes De Souza; Slomsky, Valmor; Slomski, Vilma Geni; Segura, Liliane Cristina
This study highlights the management excellence practices used in third sector organisations under the MEM - management excellence model. The research is descriptive with a quantitative approach based on a structured and self-administered questionnaire (sent via e-mail through Google Forms platform), with 28 adaptive statements from the MEM (FNQ, 2015), eight categories in an interdependent way, with 100 (one hundred) largest non-profit organisations in Brazil, by the parameter of the number of employees, in the register of the virtual platforms ONGs Brazil and the Map of Organisations of Civil Society (MOSC). It is concluded that, based on the analysis of correspondence of the practices of the management process versus social performance, in relation to the ideal parameters of full service, the research data pointed to the challenge of the organisations studied in implementing in their internal processes accounting management practices financial planning and budgeting, and integration with planning; practices for the management of asset financing by third party capital, identifying the percentage of onerous liabilities and, finally, the monitoring of the percentage of unit investment per project.